Heat Transfer: Volume 1 2008
DOI: 10.1115/ht2008-56244
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Modeling for Carbon Nanofiber Breakdown

Abstract: Carbon nanofibers (CNF) are proposed for electrical interconnect applications because of their relatively large current capacity and ability to form well-aligned one-dimensional structures. It is experimentally determined that nanofibers that are suspended between two electrodes breakdown at or near the nanofiber center. Based on published property values a simple model is used to calculate the temperature and quantify the effect of heat generation at the CNF/electrode interface on the nanofiber temperature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The 2D model solutions are compared with a simplified model developed for similar 1D systems [32][33][34]. The model previously presented is the 1D simplification of the model proposed in this work which is applicable when temperature dependence in y can be neglected, i.e., @ 2 DT @y 2 ¼ 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D model solutions are compared with a simplified model developed for similar 1D systems [32][33][34]. The model previously presented is the 1D simplification of the model proposed in this work which is applicable when temperature dependence in y can be neglected, i.e., @ 2 DT @y 2 ¼ 0.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in overall thermal resistance of unit area under the narrow line occurs because of an increase in thermal contact resistance possibly due to thermal expansion, increased scattering, and=or variation in the fabrication of the thin film. Full 3D numerical results have shown that to achieve the measured temperature at the midpoint and a parabolic local temperature profile, a significant contact resistance on the order of the overall thermal resistance beneath the narrow line is required [19,32]. Insufficient data were collected to inspect the temperature dependence of the thermal contact resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we have presented and expanded our previous model [14] to account for the improved heat transfer to the substrate and the portion of the nanofiber in contact with the substrate. The model considers material thermal conductivity, thermal contact resistances, heat spreading through the substrate, and variations in thermal transport due to nanoscale effects.…”
Section: Discussionmentioning
confidence: 99%
“…The two significant issues in the thermal transport are the location of the energy dissipation (heat) and the paths of heat transport [14]. Electricity transport through the system dissipates energy through Joule heating over the CNF length and heating due to the contact resistance at the CNF/gold interface.…”
Section: Methodsmentioning
confidence: 99%
“…1. Since breakdown has been shown to be associated with the peak CNF temperature [6,14,15], substrate contact should enhance heat dissipation, increase the immunity to Joule heating, and hence increase J max . Recently, we have extended the previous model to capture the variation in heat transport to the SiO 2 substrate due to partial CNF contact [16].…”
Section: Introductionmentioning
confidence: 99%